Successful rapid desensitization to multiple insulin preparations in an adult with type 1 diabetes: a case report and literature review - Chen, Yuwen; Zhu, Wenwen; Chen, Guoping; Yao, Jianping (Frontiers in Endocrinology, 2026)
BackgroundInsulin allergy, although rare in type 1 diabetes (T1DM), poses a significant clinical challenge due to the indispensable role of insulin therapy. Rapid induction of insulin tolerance is critical for affected individuals, especially in acute complications such as diabetic ketoacidosis (DKA).Case presentationWe report a case of a 50-year-old male with newly diagnosed T1DM who developed type I hypersensitivity reactions to multiple insulin analogs, manifesting as localized erythema, pruritus, and induration. After conventional management, including switching insulin preparations, proved ineffective, a rapid desensitization protocol was initiated using continuous subcutaneous insulin infusion (CSII). Preceding the pump initiation, half of the estimated basal dose of insulin glargine was administered subcutaneously. CSII with insulin aspart was then started at an extremely low initial rate, with increments every 30 minutes.ResultsThe target basal infusion rate was successfully achieved within 5 hours without the use of antihistamines or corticosteroids. The procedure was well-tolerated, with no systemic or local allergic reactions. Following desensitization, the patient successfully transitioned to daily injections of glargine and pre-meal aspart insulin, with no recurrence of allergic reactions during long-term follow-up.ConclusionA CSII-based rapid desensitization protocol is a safe, effective, and efficient strategy for managing insulin allergy in T1DM, including cases with sensitivities to multiple insulin preparations. This approach is particularly suitable for patients requiring urgent insulin therapy.